Effect of valproic acid on perampanel pharmacokinetics in patients with epilepsy. (13th June 2018) - Contin, Manuela; Bisulli, Francesca; Santucci, Margherita; Riva, Roberto; Tonon, Francesca; Mohamed, Susan; Ferri, Lorenzo; Stipa, Carlotta; Tinuper, Paolo; ,
Summary: We prospectively examined the effect of antiepileptic (AED) cotherapy on steady state plasma concentrations of perampanel (PMP) in epileptic patients. We classified AEDs as strong enzyme inducers (carbamazepine, phenobarbital, phenytoin, oxcarbazepine), not strong enzyme inducers/not inhibitors (levetiracetam, lamotrigine, topiramate, rufinamide, lacosamide, zonisamide, clobazam), and enzyme inhibitors (valproic acid [VPA]). The main outcome was the comparison of PMP plasma concentration to weight‐adjusted dose ratio (C/D; [μg/mL]/mg kg −1  d −1 ) among comedication subgroups. From 79 patients (42 females, 37 males) aged (mean ± standard deviation) 33 ± 13 years (range = 12‐66 years), 114 plasma samples were collected. Twenty‐eight patients (44 samples) were cotreated with enzyme inducers (group A), 21 (27 samples) with not strong enzyme inducers/not inhibitors (group B), 21 (31 samples) with not strong enzyme inducers/not inhibitors + VPA (group C), and 9 (12 samples) with enzyme inducers + VPA (group D). PMP C/D was reduced (−56%, P  < .001) in group A (1.79 ± 0.80) versus group B (4.05 ± 2.16) and increased ( P  < .001) in group C (6.72 ± 4.04) compared with groups A (+275%), B (+66%), and D (2.76 ± 2.00, +143%). Our study documents the unpublished higher PMP C/D in patients cotreated with VPA. These findings have both theoretical relevance, suggesting better characterization of PMP metabolic pathways with ad hoc studies, and clinical usefulness in managing patients on AED polytherapy.